(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In this context, the infant's birth weight is considered to be one of the most reliable and significant health markers for assessing the infant's overall health. Low birth weight is one of the most prevalent health issues in the world today, as defined by the World Health Organization (WHO), which identifies it as occurring in infants with a birth weight of less than 2,500 grammes. The research on women's lifestyles during pregnancy and their influence on the weight of their babies at birth was carried out using a variety of different materials and methods. The primary goals of the study were to determine how women's lifestyles change during pregnancy and how much of an impact lifestyle has on the weight of newborns. The design of the study was a retrospective one. The approach of purposive sampling was utilised in order to pick seventy-five moms who had normal deliveries at Krishna Hospital in Karad. The information was gathered by conducting interviews according to a predetermined schedule. The analysis of the data included both descriptive and inferential statistical methods. Results: There was a significant association found between eating a diet that included meat and other animal products, the number of meals eaten in a day, the frequency of eating food from outside, the number of times going outside with relatives, and the number of visits to friends' homes, all of which were related to the birth weight of the baby (P 0.0001). The researchers came to the conclusion that the way of life of pregnant women has an effect on the amount of weight their babies are born weighing.